2015
DOI: 10.1155/2015/630816
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Ventriculoperitoneal Shunt Infection due toCyberlindnera fabianii

Abstract: Fungal infections in the central nervous system (CNS) are associated with significant morbidity and death. Transient fungemia in immunocompetent patients without any other risk factors for fungemia has been suggested as a possible mechanism that may lead to serious fungal ventriculoperitoneal (VP) shunt infections, but evidence is lacking. The clinical spectrum, diagnosis, and optimal therapy of Cyberlindnera fabianii infections remain to be determined. We describe the first case of CNS infection due to C. fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(59 reference statements)
1
10
1
Order By: Relevance
“…According to our results of API 20 C and Vitek 2 using eleven isolates of Cy. fabianii, two isolates were identified as Candida utilis and the rests of them were Candida pelliculosa (Table 1), which was consistent with the study of Baghdadi et al [14]. That study revealed that Vitek 2 with ID 32 C system misidentified Cy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to our results of API 20 C and Vitek 2 using eleven isolates of Cy. fabianii, two isolates were identified as Candida utilis and the rests of them were Candida pelliculosa (Table 1), which was consistent with the study of Baghdadi et al [14]. That study revealed that Vitek 2 with ID 32 C system misidentified Cy.…”
Section: Discussionsupporting
confidence: 89%
“…Catheterrelated blood infections caused by Cy. fabianii have already been reported in several case studies [4,14]. Kaur et al [25] also mentioned that the frequent use of central venous catheters, urinary catheters, and prosthetic devices lead to a high risk infection of Candida species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these emerging Candida spp., C. fabianii (anamorph Candida fabianii) is one such species, which exhibits reduced susceptibility to fluconazole, itraconazole and posaconazole . Until September 2017, 21 patients with C. fabianii infection (including 14 patients with fungaemia) have been reported from different countries across Asia (n = 6), Europe (n = 12) and America (n = 3) (Table ) . Similar to our study, nearly half of these cases also occurred in paediatric age group, mostly including neonates (n = 7).…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B was used in 10 patients, mostly including those in whom the initial response to azoles was unsatisfactory . In a series of six cases from Croatia, fluconazole was used as a primary therapy followed by caspofungin in two cases and amphotericin B in one case . All the patients responded favourably with cultures becoming negative between 15 and 40 days following therapy .…”
Section: Discussionmentioning
confidence: 99%